2022
DOI: 10.1111/cpr.13337
|View full text |Cite
|
Sign up to set email alerts
|

PFKFB4 facilitates palbociclib resistance in oestrogen receptor‐positive breast cancer by enhancing stemness

Abstract: Background ER+ breast cancer (ER+ BC) is the most common subtype of BC. Recently, CDK4/6 inhibitors combined with aromatase inhibitors have been approved by FDA as the first‐line therapy for patients with ER+ BC, and showed promising therapeutic efficacy in clinical treatment. However, resistance to CDK4/6 inhibitors is frequently observed. A better understanding of the drug resistance mechanism is beneficial to improving therapeutic strategies by identifying optimal combinational treatments. Methods Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The co-administration with chemotherapy would lead to a less resistant population because TICs would have lost their stemness characteristics, as we discuss in the following paragraphs. The regulation of breast cancer progression through regulation of breast cancer stem cell-like properties has been recently described, probably mediated by the NF-κB cell signaling pathway [82,83], and the connection between chemoresistance, mesenchymal plasticity, and cancer stem cells in metastasis origin [84][85][86][87][88].…”
Section: Discussionmentioning
confidence: 99%
“…The co-administration with chemotherapy would lead to a less resistant population because TICs would have lost their stemness characteristics, as we discuss in the following paragraphs. The regulation of breast cancer progression through regulation of breast cancer stem cell-like properties has been recently described, probably mediated by the NF-κB cell signaling pathway [82,83], and the connection between chemoresistance, mesenchymal plasticity, and cancer stem cells in metastasis origin [84][85][86][87][88].…”
Section: Discussionmentioning
confidence: 99%
“…PFKFB4 enhances cancer stemness and contributes to chemoresistance to palbociclib in estrogen receptor–positive breast cancer [ 7 ]. PFKFB4 is involved in chemoresistance to sunitinib in clear-cell renal cell carcinoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphofructokinase-fructose bisphosphatases (PFKFBs), a family of bidirectional glycolytic enzymes, modulate the formation and degradation of fructose-2,6-bisphosphate (F-2,6-BP), thereby regulating glycolysis [ 7 ]. PFKFBs is encoded by four genes ( PFKFB1 , PFKFB2 , PFKFB3 , and PFKFB4 ) in humans [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD36 has been shown to be involved in the regulation of the SASP [ 81 ]. Furthermore, in a study of ER+ breast cancer, Pingping Shen et al [ 82 ] reported that MCF-7 breast cancer cell lines treated with CDK4/6 inhibitors generally experience senescence and subsequently exhibit increased expression of stemness-related genes. Moreover, they established the relationship between PFKFB4 (a rate-limiting enzyme involved in the cell glycolysis metabolic pathway, with dual functional activities of kinase and phosphatase) and breast cancer cell stemness.…”
Section: Changes In Cellular Metabolism After Senescence Promote the ...mentioning
confidence: 99%